Integrated nutrient management using deoiled Jatropha cake for sustained and economic food production - Wani, S.P.; Chander, G.; Sahrawat, Kanwar Lal; Rao, P.N. (EBSCO, 2014)
With growing environmental and energy concerns, Jatropha plantations are promoted in degraded/waste lands for the biodiesel production. Nutrient rich nonedible deoiled seed cake, a by-product of Jatropha left out after oil extraction was evaluated at the ICRISAT centre at Patancheru, India as an environment friendly source of nutrients for rainy season maize and soybean followed by postrainy chickpea in rainfed systems. Deoiled cake as partial (50%) or full replacement of recommended basal nitrogen (N) was found superior in terms of increased crop yield over the equivalent chemical fertilizers treatments. Highest yield and net returns under full replacement of basal N for maize, while under 50% basal N replacement in case of soybean and chickpea crops were recorded by 8 to 27% in grain yield and 10 to 28% in straw yield. Deoiled Jatropha cake as a full replacement of N dose in maize also recorded higher N uptake and use efficiency in maize than chemical N source treatment along with increased organic C and nutrient contents in post-harvest soil samples. This study revealed the benefits of Jatropha deoiled seed cake as a good source of plant nutrients and soil organic C in the semi-arid tropics in addition to enhanced C sequestration under Jatropha plantation on degraded waste lands.